The Dotting of “e”. Ordering Digital Literature - Pisarski, Mariusz (Porównania, 2021)
Poszerzanie pola literackiego. Studia o literackości w internecie by Elżbieta Winiecka is an important, concise summary of almost 20 years of research and artistic practice within the emerging field of electronic literature in Poland and worldwide. Its most important contribution lies in bridging the gap between traditional literary studies and new paradigms introduced by digital culture. The book’s conclusion is optimistic and goes against the notion of the end of literary studies in the era of post-literature. Within 10 chapters the author demonstrates how new ways of reading, writing and participating in literary life on the Web open up fascinating challenges for literary studies. In the review, an educational aspect of the book as well as an effort to expand the category of electronic literature by including “traditional” forms informed by the effects of digital communication are also brought forward.